Alienação fiduciária de produtos agropecuários no financiamento do agronegócio - Rodrigues, Rafael Molinari (2015)
This study has the purpose of analyzing the possibility of constituting fiduciary alienation over farming products as guarantee to the financing of the Brazilian agribusiness. For this purpose, we have divided this paper in three big parties. Firstly, in order to contextualize this study, we have mentioned brief considerations about the Brazilian agribusiness, its importance to the country and to the world, and indicated an overview about the public and private financing of the activities related to the agribusiness sector. Also as a background to reach the purpose of this study, we have established in the second chapter some notions about the historical origin of the fiduciary alienation and, further, we highlighted the types of fiduciary alienation as guarantee, its legal bases and requirements, as well as we pointed out the main advantages of the fiduciary alienation as guarantee before pledge and mortgage. After this important part of contextualization, the research follows in the last chapter with a detailed analysis of the doctrinaire and jurisprudential understandings consolidated in the 1990s and until today applicable, regarding the supposed impossibility of fiduciary alienation of fungible, consumable and alienable (in stock) movable goods, as it would be the case of the farming products. After that, we propose a reanalysis of such understanding, mainly based on the legislative evolution of the fiduciary alienation as guarantee in the Brazilian legal system in the last decades and on new jurisprudence about the issue, to then defend the possibility of the fiduciary alienation over fungible, consumable and alienable movable goods. Finally, we highlight existing peculiarities and special legislation about the fiduciary alienation of farming products and we conclude that is possible the constitution of fiduciary alienation as guarantee over farming products to the financing of the agribusiness, both when those products are fungible, consumable and alienable (in stock), and in case such farming products are duly individualized, thus, they have become not fungible products